First report of Crematogaster acuta (Fabricius, 1804) (Hymenoptera: Formicidae) in association with palm-aphid on solitary açaí palm seedlings (Euterpe precatoria Martius) in Acre, Brazil - Bona, Ketlen; Santos, Rodrigo S.; Fontenele, Luane K.; Souza, Kauã M. de; Feitosa, Rodrigo M.; Schmidt, Fernando A. (Entomological Communications, 2026)
Ant-hemipteran mutualisms are widespread in tropical ecosystems yet remain undocumented in many Amazonian plant species. Here, we report the first record of a trophobiotic association between the acrobat ant Crematogaster acuta (Fabricius, 1804) and the palm-aphid Cerataphis brasiliensis (Hempel, 1901) on seedlings of Euterpe precatoria Martius, 1842 (Arecaceae) in the state of Acre, Brazil. Ants were observed tending aphid colonies, collecting honeydew, and exhibiting protective behaviors against potential predators. This novel record adds to the growing knowledge of ant-aphid interactions in Amazonian palms and suggests potential ecological implications for aphid persistence and solitary açaí palm seedling health.